âAKTA OTENTIK RAPAT UMUM PEMEGANG SAHAM (RUPS) YANG DILAKUKAN MELALUI MEDIA TELEKONFERENSI DAN KEKUATAN PEMBUKTIANNYA - , WARDANI RIZKIANTI, Dr.Sulistiowati, S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to identify and understand the mechanism of creation and the strength of evidence of Authentic deed of the General Meeting of Shareholders (GMS) which is conducted through media teleconference. This study uses empirical juridical approach by taking some literatures to obtain secondary data